Chinese Undergraduates’ Perspectives of an Emergency Shift to Online English Instruction during COVID-19 Pandemic in Wuhan - Tang, Xiaofei; Liu, Yingliang (Palgrave Macmillan, 2022)
The COVID-19 pandemic has created significant challenges for global higher education institutions, which serve to accelerate an emergency shift from traditional face-to-face instruction to online instruction. This raises questions about whether the Emergency Remote Teaching (ERT) is perceived as satisfactory by students. This study reports on a case of Wuhan University of Technology’s ERT practices, investigating 59 Chinese undergraduates’ learning experience of English Writing A2 over 16 weeks from February to June 2020 through mixed methods. The investigation was conducted via an online questionnaire and semi-structured interviews. Major results showed that the vast majority of students held a positive attitude towards the implemented ERT-based course. Pedagogical reflections were further provided in relation to technical infrastructure, online learning platforms, and preparedness of universities and teachers.